Digitisation of Health and Safety can improve the effectiveness of prevention towards Vision Zero: some case studies - Alfredo Soeiro (2022)
Introduction to digital transformations endorse the development of the project management profession in the region strengthen the cooperation among SENET countries in development of PM practices/profession learn about the recent trends in project management provide a closer connection between digital transformation and project management context, interpersonal relationships, education and practices share experiences and practices suitable and proven in project management present new ideas, concepts, methods and tools gathered through research or practice provide stronger visibility of the project management profession in the region